Research of truck train aerodynamic indicators by using computer simulation (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article describes the possibility of studying aerodynamic parameters of a freight train using computer simulation. This method of research can reduce the costs of designing new structures of road trains and determine the optimal design features of the car's modification with insignificant costs. In order to reduce the cost of cargo transportation, some manufacturing companies apply the method of reducing and improving aerodynamic performance and installing new economical engines. Improved aerodynamics by some of the manufacturers provides fuel savings of up to 3% for long-distance and regional transportation. In order to improve aerodynamic performance (reduction of air resistance) of a road train, its shape was analyzed, taking into account possible side winds affecting the car body
Keywords: aerodynamics; road train; tail bag; rear wing; wing skirt